Schwannoma in the nasal cavity: A benign nerve sheath tumor at an odd location - Kuppusamy, Thilagarani; Ajith Prasad, Sowmya Devi; Kalyanasundaram, Balakrishnan (Indian Journal of Case Reports, 2024)
Schwannomas are neurogenic tumors arising from the Schwann cells present in the neural sheath of the myelinated nerves. These are benign tumors that can arise anywhere in the body. Schwannomas are rarely seen in the nose and paranasal sinuses representing